Investigations Concerning the Maximum Filling Degree of Dangerous Goods Packagings for Hazardous Liquids. Issue 8 (19th April 2016) - Schlick‐Hasper, Eva; Goedecke, Thomas; Kraume, Matthias
Abstract : The dangerous goods regulations UN/ADR 6.1.5.5.4 (a) prescribe a maximum filling degree for determining the test pressure for the hydraulic pressure test by real measurements. The assumption is that the maximum filling degree of the liquid phase is the worst case concerning the gauge pressure. Therefore, the main objective of this study is to investigate the effect of the filling degree on the gauge pressure. Gauge pressure measurements and calculations for different substances were carried out at different filling degrees for a steel drum and a steel jerrican (heating up from 15°C to 55°C). The assumption that the maximum filling degree is the most critical is only valid for relatively rigid packagings: If the relative expansion of the packaging is smaller than the volume increase of the liquid phase due to heating up, the gauge pressure increases with increasing filling degree. But the opposite is true for relatively flexible packagings: If the relative expansion of the packaging exceeds the relative volume expansion of the liquid, the gauge pressure increases for decreasing filling degrees. The current regulations for the hydraulic test pressure determination at a maximum filing degree do not lead to the intended safety level. For a lower level than the maximum filling degree, the prescribed safety factor of 1.5 is not respected. Under transport conditions, it is possible that the inner gauge pressure exceeds the test pressure. This can result in a failure of the packaging. There is a need to reconsider the regulations. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The dangerous goods regulations UN/ADR 6.1.5.5.4 a) prescribe a maximum filling degree for determining the test pressure for the hydraulic pressure test by measurements. The assumption is that the maximum filling degree of the liquid is the worst case concerning the gauge pressure. But if the relative expansion of the packaging exceeds the relative volume expansion of the liquid, the gauge pressure increases for decreasing filling degrees. Therefore the current regulations do not lead to the intended safety level.